Positive Obligations under the European Convention on Human Rights Within and Beyond Boundaries - Stoyanova, Vladislava (Oxford University Press, 2023)
This book identifies and explains the key analytical issues (state knowledge, causation, and reasonableness) that need to be considered in determining whether a State is responsible under the European Convention on Human Rights for omissions. In addition to this technical analytical question, the book also reflects upon what is at stake for the political community when the triggering, the content, and the scope of positive human rights obligations are determined. A central question is then how the search for a balance between intrusion and restraint by the State, between protection and freedom from invasion, defines this community and pulls the analysis of state responsibility for omissions in different directions. Designed to become the main reference source concerning ECHR positive obligations, this book makes four main contributions. First, it covers an important gap by isolating and studying the separate analytical elements (state knowledge, causation, and reasonableness) underlying state responsibility for failure to fulfil positive obligations. It explains the structure of review, the analytical steps taken to ascertain state responsibility for omissions. Secondly, the book offers a serious appreciation of the dangers associated with positive obligations whose scope might be too expansive or content too intrusive. Thirdly, it explains the different types of positive obligations. Fourthly, it offers the first examination of the conceptual hurdles if positive obligations under the ECHR were to be applied extraterritorially.